Cyclohexanethiol separation from kerosene oil by red mud - Singh A.P.; Singh P.C.; Singh V.N. (My University, 2025)
The transfer of cyclohexanethiol from kerosene oil to unconventional adsorbent, red mud and the influence of variation in agitation rate, concentration and temperature on separation by adsorption technique has been investigated. The maximum transportation of sulfur compound from oil containing 730.67 mg dm−3 (0.025% by weight sulfur) of cyclohexanethiol was noted at 45°C. The adsorption follows first order kinetics and is a diffusion controlled process. The applicability of Langmuir isotherm indicates monolayer coverage of sulfur on the outer interface of red mud. Calcination of red mud and thermodynamic parameters suggest the favorable separation of cyclohexanethiol from kerosene oil by adsorption. Copyright © 1993 Society of Chemical Industry